The large-scale structure of 3C 31 - Laing, R; Parma, P; Murgia, M; Feretti, L; Giovannini, G; Bridle, A; Perley, R (2002)
The results of a multifrequency VLA imaging study of the nearby radio galaxy 3C 31 are briefly summarized. The transition between jets and lobes is much more complex than was apparent from earlier observations, and is associated with significant variations in spectral index. We demonstrate that the known depolarization asymmetry in 3C 31 is caused by foreground Faraday rotation in the halo of the host galaxy, but the details of the associated field and density structure are not yet clear.